MESIN PERONTOK TANGKAI LADA BERKAPASITAS PRODUKSI 40 KG PER JAM - Sugianto, Sugianto; Sukamto, Sukamto (Universitas Muhammadiyah Metro, 2012)
Abstrack: The process shedding is still less effective until now, especially in Bangka-Belitung. The peppers which has been harvested be collected into the sack, after that it is continued to the process of soaking, washing and drying. In fact, it is less efficient because of the collected peppers are still with their stalks. The pepper thresher machine is a rubber roller construction machine system, which in tied up in the thresher shaft. This machine is operated with an electric motor. It is expected that this machine can help the farmer in case of the pepper collecting and decrease the sacks need. One hectare area of peppers agriculture planting have 2.500 peppers tree and they can produces 200 sack peppers before fall off by the stalk. The soaking process of peppers wich stalk peppers together having a need off many sacks. For two hundreds sack pepper with stalk only use 130 sack on peppers without stalk. So the process increase efficiency of using sack until achievement about 30%. Key words : peppers, sacks, rubber and soaking.